2015
DOI: 10.1002/2015jb012364
|View full text |Cite
|
Sign up to set email alerts
|

Geyser eruption intervals and interactions: Examples from El Tatio, Atacama, Chile

Abstract: We compare and contrast data collected in 2012 and 2014 from the El Tatio geyser field, Chile. We identify geyser systems that evolve over time, including changes in the interval between eruptions, development of new thermal features, and interactions between geysers. We study three different cases: (a) an isolated geyser, which is periodic and has nearly identical eruptions every cycle; (b) a geyser and coupled noneruptive pool, where the geyser has nonregular cycles and several preplay eruptions before the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 39 publications
4
54
1
Order By: Relevance
“…In fact, drifting of the IBE over annual and decadal timescales is typical of geysers (e.g., Barth 1940). In the same El Tatio geyser field, there is a geyser that had regular eruptions in 2012 (Namiki et al 2014) but became bimodal in 2014; this same geyser also has regular preplay events, and the interval between preplay events did not change over this time period even though the IBE of main eruption varied (Munoz-Saez et al 2015b).…”
Section: Response Of Geysers To External Influencesmentioning
confidence: 95%
See 3 more Smart Citations
“…In fact, drifting of the IBE over annual and decadal timescales is typical of geysers (e.g., Barth 1940). In the same El Tatio geyser field, there is a geyser that had regular eruptions in 2012 (Namiki et al 2014) but became bimodal in 2014; this same geyser also has regular preplay events, and the interval between preplay events did not change over this time period even though the IBE of main eruption varied (Munoz-Saez et al 2015b).…”
Section: Response Of Geysers To External Influencesmentioning
confidence: 95%
“…Uncontroversial is the observation that regional and distant earthquakes can change the IBE (e.g., Marler 1964, Marler & White 1975, Hutchinson 1985, Husen et al 2004 or initiate a switch from a unimodal to a bimodal IBE (Silver & Valette-Silver 1992). Nearby geysers can also influence each other-through pressure changes in the subsurface (e.g., Ingebritsen & Rojstaczer 1996, Munoz-Saez et al 2015b. Based on several years of continuous data, it was shown that several of Yellowstone's geysers display seasonal cycles of eruption intervals resulting from variations in the hydrological cycle and/or weather (Marler 1954;Hurwitz et al 2008Hurwitz et al , 2012.…”
Section: Response Of Geysers To External Influencesmentioning
confidence: 96%
See 2 more Smart Citations
“…Geyser eruption dynamics can be influenced by changing pressure‐temperature conditions. At El Tatio a major eruption occurred if bubble addition was sustained (Munoz‐Saez, Namiki, & Manga, ) and the water in the upper conduit was heated enough (Namiki et al, ). Multiple minor eruptions therefore preceded a major eruption (Munoz‐Saez, Namiki, & Manga, ).…”
Section: Introductionmentioning
confidence: 99%